O002 Medical therapy for sleep disordered breathing in children: a randomised, double-blind placebo-controlled trial. (7th October 2021) - Baker, A; Grobler, A; Davies, K; Griffiths, A; Hiscock, H; Kubba, H; Peters, R; Ranganathan, S; Rimmer, J; Rose, E; Rowe, K; Simpson, C; et al.
Abstract: Background: Sleep Disordered Breathing (SDB) in children is characterised by snoring and breathing difficulties during sleep. Small clinical trials suggest intranasal corticosteroids reduce SDB severity as defined by polysomnography. We assessed the efficacy of intranasal corticosteroid for improving symptoms and quality of life (QOL) in children with SDB. Methods: This is a double-blind, randomised, placebo-controlled trial of healthy children 3-12y referred to a specialist with SDB symptoms. Exclusions were previous adenotonsillectomy, obesity or severe SDB. Participants received daily intranasal mometasone furoate 50micrograms or normal saline for 6 weeks. The primary outcome was resolution of symptoms measured by SDB score. Secondary outcomes were SDB symptom scores, QOL, behaviour, parent and surgeon perceived need for surgery, and parent satisfaction with treatment. Results: 276 participants were recruited; 138 in each group. 127 and 123 participants had primary outcome data at 6 weeks in the mometasone and saline groups respectively. Baseline age, atopic history, symptom severity and QOL were similar between groups. Resolution of SDB symptoms occurred in 44% [95%CI 35–53] of the mometasone group and 40% [95%CI 32–49] of the saline group; risk difference 4% [95%CI -0.8–16] p=0.511. Secondary outcomes were not different between groups. Discussion: This large RCT, using clinical rather than polysomnographic outcomes to investigate the efficacy of mometasone on symptoms of SDB, found substantial rates of symptom resolution after 6 weeks in both groups. However, we found no difference in treatment effect between 6 weeks of intranasal mometasone over saline, for management of SDB symptoms in childhood.